Karnivalisasi Bakhtin: Perlawanan Kekuasaan dalam Novel Genduk Duku Karya Y.B Mangunwijaya - Zaira Aulia Nurjanah; Cecep Dudung Julianto; Lina Siti Nurwahidah (Program Studi Pendidikan Bahasa Program Pascasarjana Universitas Negeri Jakarta, 2026)
ABSTRACT This study analyzes Bakhtin’s Carnivalization in relation to the Representation of Repressive Power in the novel Genduk Duku by Y.B. Mangunwijaya. The research employs a qualitative paradigm with a Sociology of Literature approach, specifically focusing on Mikhail Bakhtin’s theory of Carnivalization. The formal object of this study is Mikhail Bakhtin's Carnivalization, while the material object is the novel Genduk Duku. The research problem centers on the forms of Bakhtinian Carnivalization manifested within the novel. The objective of this research is to identify the forms and representations of character carnivalization in Genduk Duku as a response to the representation of the Mataram rulers repressive power. The findings demonstrate that there are four categories of carnivalization utilized as a form of implicit resistance: (1) Familiar and free interaction between people, representing the dissolution of social hierarchies which allows the critical voices of the lower class to be acknowledged by the elite; (2) Eccentric behavior, manifested through unconventional actions to subvert or deflect the repressive will of the upper class; (3) Carnivalistic mésalliances, which unite the sacred and the profane to dismantle the authority and prestige of the ruling class; (4) Sacrilegious, in the form of acts of blasphemy against the upper class. Keywords: Bakhtin’s Carnivalization; Genduk Duku Novel; Implicit Resistance;Repressive Power; Sociology of Literature